Rancang Bangun Sistem Monitoring dan Kendali Ketinggian Air Tandon Berbasis IoT Menggunakan ESP32 dan Blynk - Fikko Nanda Ramadhani; Nasywa Hamna Zakiya (Tech : Journal of Engineering Science, 2026)
Clean water management often faces obstacles such as overflowing water reservoirs or pump damage due to limited manual monitoring. This study aims to design and implement an automatic water reservoir monitoring and control system based on the Internet of Things (IoT). The method used is a prototype method that includes the identification, design, and repeated testing stages. The hardware architecture consists of an ESP32 microcontroller, an HC-SR04 ultrasonic sensor, a relay, a buzzer, and a manual drain tap connected to a 300 ml reservoir, integrated with the blynk cloud platform. The sensor measures the distance to the water surface which is converted into volume using the formula V = ((H - d)/H) x Vmax. The test results show that the system successfully classifies water levels into three categories: "Low", "Medium", and "Full" with good accuracy. The pump operates automatically when the water is low and reaches a stable off state at a threshold of 6 cm to prevent overflow, while the manual drain tap allows users to drain excess water as needed. Additionally, the system provides real-time monitoring and manual control through a low-latency smartphone interface. In conclusion, the implemented IoT system effectively overcomes manual monitoring challenges, improves water efficiency, and provides users with reliable remote control access.